Balanced scorecard for future sustainability of Malaysian higher education institutions - Mohd Ali, Hairuddin; Ayodele, Lasisi Abass (Future Academy www.FutureAcademy.org.UK, 2018)
The purpose of this study is to examine the relationship between Balanced Scorecard Initiatives and Organizational Climate with regard to the Sustainability of Malaysian Higher Education Institutions. A sample of 272 top administrators from eight selected public universities in Peninsular Malaysia was determined based on purposive sampling technique. A full-fledged Structural Equation Modeling computer software, Analysis of Moment Structures version 20.0 was used as statistical analysis technique in examining the psychometric properties, testing the hypotheses of the study. Using a comprehensive Balanced Scorecard theory this paper argues that Balanced Scorecard Initiatives provide a systemic strategy for the achievement of future sustainability of Malaysian higher education institutions. The findings revealed that Organizational Climate has no relationship with Sustainability of Malaysian Higher Education Institutions and therefore consistent with previous literature due to communication challenges and decisionmaking in higher education institutions that needs further attention among the selected eight higher education institutions in Malaysia. This study provides a basis for the future study but unfortunately the result cannot be generalized for the whole of Malaysia due to the study is limited to peninsular Malaysia only. The framework presented in this study can be used as a basis for the development of general framework of the Balanced Scorecard, Organizational Climate and the Sustainability of Higher Education Institutions perspectives. This paper indicates the important findings on the Balanced Scorecard Initiatives and considered as first kind of research on the future sustainability of Malaysian higher education institutions.